2012
DOI: 10.1094/pdis-09-11-0746-re
|View full text |Cite
|
Sign up to set email alerts
|

Relative Susceptibility Among Alternative Host Species Prevalent in the Great Plains to Wheat streak mosaic virus

Abstract: Ito, D., IVIiller, Z., Menaüed, F., Moffet, M., and Burrows, M. 2012. Re!ative susceptibiüty among a!temative host species preva!ent in the Great P!ains to Wheat streak mosaic virus. Plant Dis. 96:1185-1192.Wild grasses, crops, and grassy weeds are known to host Wheat streak mosaic virus (WSMV) and its vector, the wheat cur! mite (WCM). Their relative importance as a source of WSMV was evaluated. A survey of smaü-grain fie!ds throughout Montana was conducted between 2008 and 2009. Cheatgrass was the most preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 42 publications
(25 reference statements)
0
24
0
1
Order By: Relevance
“…A WSMV isolate from Conrad, MT (Conrad I) was used as the standard isolate for this studies (13). Isolate stocks were maintained at -80°C until use.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A WSMV isolate from Conrad, MT (Conrad I) was used as the standard isolate for this studies (13). Isolate stocks were maintained at -80°C until use.…”
Section: Methodsmentioning
confidence: 99%
“…Plants were maintained as described by Ito et al (13). Two weeks after inoculation, these stock plants were used to inoculate flats (35 by 50 cm) of spring wheat at growth stage Feekes 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hunger et al (1992) reported a nonsignificant yield reduction (3 to 23%) in spring inoculation, a trend that was similar to our mechanical inoculation of Overland (13%), but these incidences are much lower compared with the 55% yield loss observed in this study with mite inoculation. Ito et al (2012) reported higher incidence of WSMV in barley (88%) with mite inoculation, while Lehnhoff et al (2015) reported very poor infection (average 13%) when barley was mechanically inoculated with WSMV under field conditions. The average yield losses due to mite inoculation in this study are generally greater but those due to mechanical inoculation are within the 32 to 74% reported in other studies that used mechanical inoculation in susceptible cultivars (Byamukama et al 2014;Fahim et al 2012;Miller et al 2014;Sharp et al 2002).…”
Section: Discussionmentioning
confidence: 96%
“…In addition, information on the effects of inoculation method (mites versus mechanical) on disease intensity and yield will be useful to researchers comparing response of wheat cultivars to WSMV infection. Laboratory experiments revealed a higher incidence of WSMV in barley plants inoculated using WCM compared with mechanical inoculation in the field (Ito et al 2012;Lehnhoff et al 2015), indicating that the method of inoculation can influence disease severity. A similar study by Miller et al (2014) revealed severe symptoms and yield loss in wheat plants mechanically inoculated with WSMV in the spring but not those inoculated during the fall.…”
mentioning
confidence: 99%